Investigating the Role of ICT toward Students' Higher Order Thinking in Writing Skills at Islamic University Students - Eka Apriani; Santiana Santiana; Hendra Harmi (STAI Hubbulwathan Duri, 2022)
This study gave focused on ICT used by students in writing, the role of ICT toward students' higher-order thinking, and the dominant role of ICT toward students higher-order thinking. Samples of this research were English students of South Sumatra Islamic universities, namely UIN Raden Fatah Palembang, IAIN Curup, IAIN Bengkulu, UIN Jambi, UIN Lampung, and UIN Bangka Belitung. There were 30 English students from every university used as the research sample of this study. The survey research design was used in this study. The researcher used an online questionnaire to find out the data about the role of ICT toward HOTS in writing skills. The data was analyzed by using percentage analysis (SPSS 25). The result showed students gave positive opinions when their lecturer used ICT in improving their Higher-Order Thinking in Writing skills (71.8%). This percentage is at a good level.